Nano-biodegradation of plastic materials - Leão, Alcides Lopes [UNESP]; Cesarino, Ivana [UNESP]; de Souza, Milena Chanes [UNESP]; Dias, Otavio Augusto Titton; Jawaid, Mohammad (Elsevier, 2022)
The role of nanotechnology in the fabrication of next-generation nanocomposites based on cellulose derivatives has been suggested to be an important factor in advanced modern technologies for reinforcement purposes and for functional tunability. In this context, nanotechnology has attracted much attention with respect to its promising properties and broad range of applications in several fields such as structural components, ballistic protection, electronics, food science, and drug delivery. It is well established that incorporation of nanoparticles into polymer matrices can improve certain properties of the nanocomposites. However, the influence of the chemical characteristics of the nanofillers on the biodegradability properties of the nanocomposites is not fully understood. This chapter proposes a comprehensive understanding on the effect of cellulose-based nanoparticles on biodegradation properties of a variety of nanocomposite materials. The trade-off between biodegradability and stability of the material is still challenging. The appropriated balance between them will be studied to design robust and sustainable products. Future applications are envisaged to exploit the degree of biodegradability of nanocomposites for more economically viable routes, paving way for cost-effective and sustainable bio-based and biodegradable plastics.
Keywords: Biodegradability; Biopolymers; Cellulose; Nano-fillers; Nanocellulose; Nanotechnology